Unlocking sustainable competitive advantage: exploring the impact of technological innovations on performance in Mexican SMEs within the tourism sector - León-Gómez, Ana María; Santos Jaén, José Manuel; Palacios-Manzano, Mercedes; Garza-Sánchez, Héctor Horacio (Springer Nature, 2023)
This research inquiry explores the interplay between environmentally sustainable practices, technological innovations and small- and medium-sized enterprises (SMEs) performance in Mexico's tourism sector. The tourism industry in Mexico holds immense economic significance, contributing significantly to employment and revenue generation. However, the sector also faces challenges related to environmental sustainability. Thus, the objective of this research is to assess how the integration of sustainable environmental practices influences the operational outcomes of SMEs. Furthermore, it also aims to conclude the role of technological innovation, Information and Communication Technology (ICT), digitalization and gender in this relationship. A structural equation modeling approach was applied to a sample of 797 Mexican SMEs in the tourism sector. Our findings provide evidence of several contributions: first, environmental sustainability practices improve performance; second, technological innovation, ICT and digitalization play a critical mediating role in specific relationships to foster performance; finally, incentives encourage sustainable practices related to environmental improvement, especially when the SME's CEO is a woman. The results of this study hold practical significance for the SME sector, as it demonstrates that by adopting sustainable practices, SMEs can strengthen their market position, improve technological innovativeness, minimize environmental impact and capitalize on emerging business prospects.
Keywords: Finanzas; Contabilidad; Environmental sustainability; Technological innovation; Performance; PLSSEM; Information and communication technologies (ICT); Digitalization